Reinforcing Factor Perilaku Seks Pranikah pada Remaja SMA Favorit di Kota Padang - Aprianti Aprianti; Dien Gusta Anggraini Nursal; Yudi Pradipta (Media Kesehatan Masyarakat Indonesia, 2020)
The number of adolescent premarital sex behavior cases in West Sumatera was 107 in 2016, where 80% occurred in Padang. This research aims to know the reinforcing factor that related to premarital sex behavior on adolescent of Senior High School favorite in Padang. Quantitative research with cross-sectional design. The number of samples was 547 taken by proportional stratified random sampling. The data are collected by questionnaire and analyzed with univariate, bivariate, and multivariate logistic regression. Moreover, qualitative research with case study design with informants is eight students and teachers respectively. Data collected with in-depth interviews then analyzed with thematic content. More than half of the respondents have a high risk of sexual behavior. Bivariate analysis showed that there were correlation role of teacher (p= 0,025), role of friends (p= 0,0001), role of parent (p= 0,012), and there was no correlation role of health provider (p= 0,075) with adolescent premarital sex behavior. Multivariate analysis showed that variable with a high correlation to premarital sexual behavior was the role of friends (p= 0,000, Ecp(B)= 2,743) with controlled by predisposing variables (knowledge, attitude, religiosity) and enabling variable (mass media exposure). Therefore, the reinforcing factor that related to premarital sex behavior on adolescents was the role of friends. It was recommended that adolescents to be more selective in choosing friends who bring positive impacts and should filter the true information about premarital sexual behavior from their peers.